Indoor Carbon Monoxide: A Case Study in England for Detection and Interventions to Reduce Population Exposure. (4th April 2013) - McCann, L. J.; Close, R.; Staines, L.; Weaver, M.; Cutter, G.; Leonardi, G. S.
Abstract : Background . Potential exposure to carbon monoxide (CO) in private homes is largely unquantified. Aim . To estimate prevalence of potential exposure to CO in residential dwellings and describe associated interventions in an inner-city community. Methods . A housing association in London, Hackney Homes, began fitting CO alarms in the 22, 831 local authority homes it is responsible for in January 2010. A gas engineer investigated each alarm activation and recorded the information on a standard form. We undertook a cross-sectional study of all 22, 831 homes, using data from these forms. Descriptive analysis was performed, including incidence, monthly variation, cause of alarm activation, and actions taken. Results . Between November 2011 and April 2012, 106 incidents were reported. Of these, 34.6% identified an issue with a gas appliance, and 10.6% identified misuse of cooking methods as the cause of activation. Relevant interventions were put in place, including disconnection of the gas appliance and education around cooking methods. Discussion . Little is known about the burden of CO poisoning in residential dwellings. This study provides important information on the path to quantifying population exposure to CO as well as establishing a possible approach to access this key information and realistic interventions to reduce potential exposure.